Radioactive Contamination of Wild Mushrooms from Ukraine under Conditions of Contrasting Radiation Loads: 36 Years after the Chernobyl Nuclear Power Plant Catastrophe - Grodzinskaya, Anna A; Nebesnyi, Vitaliy B; Landin, Vladimir P; Gabriel, Jiří (International journal of medicinal mushrooms, 2022)
It has been 36 years since the Chernobyl Nuclear Power Plant catastrophe, but the consumption of wild mushrooms in Ukrainian Polissya is still dangerous since its territory is heavily contaminated by radionuclides. The aim of this study was to estimate 137Cs and 90Sr uptake in wild mushrooms from locations with contrast radioactive loads (Zhytomyr Polissya, Ukraine). In mushroom samples collected from Drevlyanskyi Nature Reserve since 2013 (average levels of soil surface contamination with 137Cs are 555-1480 kBq m-2), the highest levels of 137Cs were observed in symbiotroph species - Imleria badia (≤ 2680 kBq kg-1 dry mass [dm]), Tricholoma equestre (≤ 1420 kBq kg-1 dm), Lactarius rufus (≤ 602 kBq kg-1 dm), Sarcodon imbricatus (≤ 464 kBq kg-1 dm), Leccinum scabrum (≤ 117 kBq kg-1 dm), Suillus bovinus (≤ 118 kBq kg-1 dm), and Boletus edulis (≤ 96 kBq kg-1 dm). 90Sr activity was significantly lower, with the highest levels detected in Russula emetica (193 Bq kg-1 dm), Daedaleopsis confragosa (145 Bq kg-1 dm), and Hypholoma fasciculare (141 Bq kg-1 dm). The 137Cs/90Sr ratio in fruiting bodies in samples ranged from 6.1 (Bovistella utriformis) to 28,979 (T. equestre). Activity concentrations in mushrooms from locations with relatively low contamination with 137Cs (18.5-27.75 kBq m-2) also reached the highest values in symbiotroph species I. badia (7698 Bq kg-1 dm), Lactarius vellereus (6072 Bq kg-1 dm), and S. luteus (1448 Bq kg-1 dm). Potential calculated annual effective doses due to mushroom consumption by adults, considering only the effect of 137Cs, reached 0.311 and 8.71 mSv in B. edulis and I. badia from highly contaminated locations, respectively, and 0.0014 and 0.009 mSv in these species from low contaminated ones.
Keywords: černobylská havárie; Agaricales; dospělí; radioizotopy cesia; Ukrajina; Cesium Radioisotopes; Soil Pollutants, Radioactive; Nuclear Power Plants; Chernobyl Nuclear Accident; lidé; radioaktivní látky znečišťující půdu; Strontium Radioisotopes; Ukraine; jaderné elektrárny; radioizotopy stroncia; Adult; Humans